Isolasi, Karakterisasi dan Potensi Bakteri Endofitik dari Tanaman Zodia (Evodia suaveolens Scheff) sebagai Penghasil Antibiotika - Melisa Ainil Fajri; Anthoni Agustien; Periadnadi Periadnadi (Universitas Andalas, 2015)
Endophytic bacterium are important to produce antibiotic. We have experimentally studied zodia plant (Evodia suaveolens Scheff) in attempting to isolate and characterize the bacterium. We have also examined potentiality of each isolate to produce antibiotic. We obtained three a isolate of endophytic bacterium that produce antibiotic compounds. Among three isolates, two could form high inhibition zone. MZS-01 formed 10.4 mm inhibition zone against Eschericia coli, while MZS-03 formed 6.96 mm inhibition zone against Staphylococcus aureus. We described the isolates MZS-01 and MZS-03 based on macroscopis and microscopis characteristic of colony culture.